2014
DOI: 10.12998/wjcc.v2.i7.284
|View full text |Cite
|
Sign up to set email alerts
|

Verrucous carcinoma of the esophagus: A case report and literature review

Abstract: Verrucous carcinoma of the esophagus is a variant of a squamous cell cancer. Our case is a 78-year-old male patient comes in with the dysphagia and weight loss, and on endoscopy (EGD) he is found to have an irregular intraluminal mass at the distal esophagus. With the deep EGD assisted biopsy, diagnosis of the verrucous carcinoma is made. Due to multiple co morbidities and possible infiltration to the pericardium, patient is taken for the esophageal stent placement and is being referred for the chemo-radiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 6 publications
0
42
0
Order By: Relevance
“…The age distribution of VC ranges from 35 to 80 years (median 61) with a male predilection (M:F = 2:1). Site distribution within the esophagus varies among lower (70%), upper (23%), and middle (7%) in various studies . As also apparent in conventional esophageal SCC, correlation of human papilloma virus (HPV) with VC has also been demonstrated in some studies, mainly HPV‐types 51 and 11 .…”
Section: Rare Variants Of Squamous Carcinomamentioning
confidence: 99%
See 1 more Smart Citation
“…The age distribution of VC ranges from 35 to 80 years (median 61) with a male predilection (M:F = 2:1). Site distribution within the esophagus varies among lower (70%), upper (23%), and middle (7%) in various studies . As also apparent in conventional esophageal SCC, correlation of human papilloma virus (HPV) with VC has also been demonstrated in some studies, mainly HPV‐types 51 and 11 .…”
Section: Rare Variants Of Squamous Carcinomamentioning
confidence: 99%
“…It was first reported in the esophagus in 1967 by Minielly et al . Since then, only a handful of esophageal cases (<30) have been reported . The age distribution of VC ranges from 35 to 80 years (median 61) with a male predilection (M:F = 2:1).…”
Section: Rare Variants Of Squamous Carcinomamentioning
confidence: 99%
“…The typical endoscopic appearance of esophageal VSCC shows shaggy, white, exophytic, wart-like, velvety, papillary, spiked and cauliflower-like mass, and the tumor occurs mainly from the middle to lower esophagus. 7,8 Westerterp et al 9 reported that the white masses that are a result of keratinization develop focal dysplasia and SCC. In addition, endoscopic ultrasonography, narrow-band imaging (NBI) and iodine-staining can each play an adjuvant role in the preoperative diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, endoscopic ultrasonography, narrow-band imaging (NBI) and iodine-staining can each play an adjuvant role in the preoperative diagnosis. 8,10 In chromoendoscopy, a dramatic color change after iodine staining, from the yellow to pink 2-3 min later, is known as the pink-color sign (PCS), which is useful for identifying cancerous lesions. 11 The PCS has been reported to improve specificity for esophageal high-grade intraepithelial neoplasia and invasive cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation